Anticandidal Effects of Ocimum basilicum and Ocimum sanctum: Unveiling in vitro and in vivo Efficacy against Systemic Candidiasis - Gupta, Saurabh; Nagar, Lokesh; Singla, Madhav; Smriti; Singh, Sachin Kumar; Gupta, Gaurav; Bhojraj, Suresh; Syed, Rahamat Unissa; Alshammari, Aliaa; Alshammari, Maali D.; Alshammari, Njoud Nahi Omer; Alshammari, Atheer Nahi Omer; et al. (Current Pharmaceutical Design, 2026)
BackgroundThis research explored the antimicrobial, antifungal, and in vivo anticandidal activities of two herbal extracts: Ocimum basilicum (HEOB) and Ocimum sanctum (HEOS). Additionally, the study analyzed the phytochemical components of these extracts.AimTo examine the efficacy of HEOB and HEOS extracts in terms of their antimicrobial, antifungal, and anti-candidal activities and analyze their phytochemical composition, antioxidant potential, and immunomodulatory properties in vivo.MethodsDried flowers and leaves from Ocimum basilicum and Ocimum sanctum were extracted using a cold maceration process with a 1:1 ethanol-water solution. Phytochemical analysis followed established protocols, and the total phenolic and flavonoid contents were measured using colourimetric methods. HPLC was used to determine the concentrations of specific compounds, including rosmarinic acid, rutin, eugenol, and quercetin. Antioxidant activity, specifically nitric oxide (NO) scavenging and antimicrobial properties, was assessed in vitro using the cup plate method. In vivo studies were conducted on immunocompromised mice with systemic candidiasis, treated with plant extracts at 200 and 400 mg/kg or with ketoconazole as a control. Survival rates, tissue histology, and leukocyte counts were evaluated, and statistical analysis was performed using ANOVA.ResultsHEOB and HEOS extracts possess strong antimicrobial and antioxidant activities, largely due to flavonoids such as rutin, quercetin, rosmarinic acid and eugenol. In vivo experiments revealed that both extracts effectively reduced fungal load, increased survival rates, and alleviated immunosuppression in mice with systemic candidiasis. The extracts also exhibited significant immunomodulatory properties by boosting cell-mediated immune responses. At higher concentrations, the antifungal performance of HEOB and HEOS was similar to that of ketoconazole.ConclusionHEOB and HEOS exhibited strong antibacterial, antifungal, and anticandidal properties, showing significant effectiveness in treating systemic candidiasis. Their immunomodulatory effects and ability to boost cell-mediated immunity make these extracts promising options for addressing systemic candidiasis, particularly in individuals with weakened immune systems. This research offers valuable insights and sets the stage for future investigations into the treatment of oral and vaginal candidiasis.
Keywords: quercetin